Pengembangan Bahan Ajar Interaktif Berbasis Game Lexgo Untuk Pembelajaran Membaca Permulaan Siswa Sekolah Dasar - Moch Ridho Saputra; Muhardila Fauziah (Science and Education Journal (SICEDU), 2026)
This study aims to develop interactive teaching materials based on the LexGo game oriented toward the PASS early reading learning model for elementary school students. This research employed a Research and Development (R&D) method using the 4D development model, which consists of define, design, develop, and disseminate stages. The research subjects included expert validators as well as lower-grade students and teachers from two elementary schools. The instruments used were validation sheets and response questionnaires from students and teachers, and the data were analyzed using descriptive percentage analysis to determine the feasibility and practicality of the product. The results showed that the developed teaching materials achieved a very high level of feasibility, with validation scores of 94.23% from teaching material experts, 90% from material experts, and 87.5% from educational practitioners. Furthermore, the practicality test indicated very practical results based on student responses of 85.21% and 85.76%, as well as teacher responses of 88.50% and 89.25% in each school. Therefore, the LexGo game-based interactive teaching materials are considered feasible and practical for early reading instruction and can effectively support the learning process in elementary schools. Keywords: interactive teaching materials, game-based learning, early reading, elementary school students